The Bequest of Books: A Hidden Biography (The Journal of the Sylvia Townsend Warner Society, 2020)
This article presents and introduces a sequence of six poems that Sylvia Townsend Warner dedicated to Valentine Ackland. Five are previously unpublished, as is the sequence as a whole. Five of the six are love poems to Valentine Ackland arising from their trips to Spain during the Spanish Civil War; in them the romantic and sexual theme is interwoven with their experience of social revolution in Barcelona. The poems are particularly important because of their unusual combination of radical politics and queer desire.